A database of aerosols and gases coefficients for VIS-NIR radiative transfer in the Solar System planetary atmospheres. (February 2019) - Oliva, F.; D'Aversa, E.; Liberti, G.L.; Sindoni, G.; Altieri, F.; Castelli, E.
Abstract: Radiative transfer (RT) modelling of planetary atmospheres allows to obtain extremely valuable information about these environments. The computation of optical properties of the aerosols and gases, that is heavily time consuming, is always required as input for both forward models and inversion algorithms. We provide look up tables for these coefficients, ready to be ingested in RT solvers, in the visible and near infrared spectral ranges and covering the main species of the Solar System planets' atmospheres. Gases absorption coefficients have been computed with the line-by-line approach from the HITRAN 2012 spectral database and an improved method to interpolate them is suggested. Aerosols single scattering properties have been computed using the Mie and Rayleigh models for a set of selected species relevant for planetary atmospheres. Optimization in terms of tabulated wavelengths and maximum number of Legendre polynomial expansion terms has been performed for each species. Highlights: Development of databases of aerosols and gases properties for radiative transfer applications. Improved interpolation method for gases absorption coefficients. Applicability of the developed databases to studies related to the atmospheres of the Solar System planets.